1978
DOI: 10.1002/jcp.1040940103
|View full text |Cite
|
Sign up to set email alerts
|

Reversible regulation by magnesium of chick embryo fibroblast proliferation

Abstract: The rate of 3H-thymidine incorporation and of cell proliferation in chick embryo fibroblast cultures are reduced coordinately when the [Mg2+] of the external medium is reduced below the physiological concentration of about 0.8 mM. These effects of moderately reduced [Mg2+] and the accompanying change in appearance of the cells, resemble the effects produced by lowering the [serum] of the medium. Cells subjected to severe Mg2+ deprivation, especially at low [Ca2+], die and detach from the culture dish. Cells ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Exposure of fibroblasts, endothelial, and epithelial cells to reduced [Mg 2þ ] e , inhibits cell proliferation whereas replacing Mg 2þ in the culture medium stimulates cell growth (Rubin and Berbie, 1978;Banai et al, 1990;Zhou and Kummerow, 1995). However, this postive correlation between Mg 2þ availability and degree of proliferation does not seem to be a homogeneous phenomenon.…”
mentioning
confidence: 96%
“…Exposure of fibroblasts, endothelial, and epithelial cells to reduced [Mg 2þ ] e , inhibits cell proliferation whereas replacing Mg 2þ in the culture medium stimulates cell growth (Rubin and Berbie, 1978;Banai et al, 1990;Zhou and Kummerow, 1995). However, this postive correlation between Mg 2þ availability and degree of proliferation does not seem to be a homogeneous phenomenon.…”
mentioning
confidence: 96%
“…The omission of either Ca2+ or Mg2+ from the medium of cultured cells inhibits metabolism and growth to varying degrees in different cell types (1)(2)(3)(4)(5)(6)(7). The effects of omitting one can be greatly intensified by reducing the concentration of the other (4,7,8), and it is not completely clear whether the two are interchangeable in some cellular function(s) or have separate roles.…”
mentioning
confidence: 99%
“…The effects of omitting one can be greatly intensified by reducing the concentration of the other (4,7,8), and it is not completely clear whether the two are interchangeable in some cellular function(s) or have separate roles. Our studies of the divalent cations have concentrated on their effects on the initiation of DNA synthesis, which is a delayed response of cells to external effectors and dependent on other cellular activities, including energy metabolism and the synthesis of RNA and protein (9).…”
mentioning
confidence: 99%
“…Additional support seemed to come from the finding that supranormal concentrations of Ca2+ stimulate the growth of quiescent 3T3 cells (12), but this has proven to be a nonspecific effect caused by insoluble complexes of Ca2+ and inorganic orthophosphate (Pi) (13,14). It has also been shown that Ca2+ deprivation in chick embryo cells causes a marked increase in the passive permeability of cells (15) and causes other changes that do not occur when cells are inhibited in a more physiological way by the withdrawal of serum or addition of cortisol (15,16 The procedures for measuring cation contents of cells by atomic absorption spectrophotometry were previously reported (20). Culture dishes (100 mm) were used in the cation determination experiments.…”
mentioning
confidence: 99%